Catalyst-dependent selectivity in the relay catalytic branching cascade - Bansode, Avinash H.; Shaikh, Aslam C.; Kavthe, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
The synthesis of small organic molecules as probes for discovering new therapeutic agents has been an important aspect of chemical biology. One of the best ways to access collections of small molecules is to use various techniques in diversity-oriented synthesis (DOS). Recently, a new form of DOS, namely relay catalytic branching cascades (RCBCs), has been introduced, wherein a common type of starting material reacts with several scaffold-building agents (SBAs) to obtain structurally diverse molecular scaffolds under the influence of catalysts. Herein, the RCBC reaction of a common type of substrate with SBAs is reported to give two different types of molecular scaffolds and their formation is essentially dependent on the type of catalyst used.
Keywords: alkynols; cascade synthesis; chemoselectivity; diversity-oriented synthesis; Homogeneous catalysis

Bi(OTf)3-promoted cascade annulation of hydroxy-pyranones and unsaturated γ-ketoesters for the construction of polycyclic bridged pyrano-furopyranones - Rathod, Akshay B.; Borade, Balasaheb R.; Sambherao, Pooja I.; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
An efficient protocol for constructing complex three dimensional polycyclic bridged chromano-furopyranones and pyrano-furopyranones (closely related to bioactive natural products) via bismuth(III)-catalyzed cascade annulation of hydroxy-pyranones and unsaturated gamma-ketoesters is presented. This process involves intermolecular Michael addition, intramolecular hemiketalization, lactonization, formation of one C-C bond and two C-O bonds, rings, and contiguous stereocenters.
Keywords: 1 3-Dicarbonyl Compounds; alkynols; Coumarins; Fungus